A Study on Impact of Merger and Acquisition on Financial Performance of Agri-Food Companies - I. Gupta; T. V. Raman (Финансы: теория и практика)
The purpose of this study is to explore the expansion of merger and acquisition (M&A) literature in the context of Indian studies and examine the impact of mergers and acquisitions on various financial performance parameters of India’s Agri-Food companies. The period of study is from 2011 to 2019, and Wilcoxon Sign Rank methodology has been used. The study hypothesized that there is significant growth in Indian literature of M&A and there is a significant difference in the operating performance, financial performance and shareholders’ return of acquiring firms during the period of pre-M&A and post-M&A. The study findings state that the literature of M&A in India increases significantly, and the operating ratio, financial ratio, and shareholder return also exhibit a significant improvement whereas the expense ratio related to the operating ratio shows no improvement in performance. The study concludes that the India Agri-Food company’s financial performance has improved overall for the acquiring firms during the post-M&A period.